2014
DOI: 10.1002/2013jg002392
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative assessment of a terrestrial biosphere model's data needs across North American biomes

Abstract: Terrestrial biosphere models are designed to synthesize our current understanding of how ecosystems function, test competing hypotheses of ecosystem function against observations, and predict responses to novel conditions such as those expected under climate change. Reducing uncertainties in such models can improve both basic scientific understanding and our predictive capacity, but rarely are ecosystem models employed in the design of field campaigns. We provide a synthesis of carbon cycle uncertainty analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
165
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 109 publications
(173 citation statements)
references
References 94 publications
7
165
1
Order By: Relevance
“…A recent study by Dietze et al (2014) likewise identified mis-parameterization of light-use efficiency at low-light levels to play a central role in biospheric model uncertainties across HL regions of North America. The study indicated that a likely source for mis-parameterization is due to greater variance in this parameter across high-latitude sites, even when these contain similar biota.…”
Section: Error Analysismentioning
confidence: 99%
“…A recent study by Dietze et al (2014) likewise identified mis-parameterization of light-use efficiency at low-light levels to play a central role in biospheric model uncertainties across HL regions of North America. The study indicated that a likely source for mis-parameterization is due to greater variance in this parameter across high-latitude sites, even when these contain similar biota.…”
Section: Error Analysismentioning
confidence: 99%
“…Before these experiments, we conducted an uncertainty analysis (LeBauer et al, 2013;Dietze et al, 2014) to choose the model parameters for calibration. The parameters that can be constrained by data are those that contribute to the model uncertainty for that corresponding variable.…”
Section: Emulator Experimentsmentioning
confidence: 99%
“…The Ecosystem Demography model v2 (ED2; Medvigy et al, 2009) is another relatively coupled model, with high sensitivity to g s . Dietze et al (2014) estimated that ∼ 10 % of the uncertainty in net primary productivity (NPP) predicted by the ED2 model across North America Biomes was directly due to the stomatal slope parameter (i.e. g 1 ).…”
Section: Implications For Other Modelsmentioning
confidence: 99%